2021
DOI: 10.1519/jsc.0000000000004101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrate Supplementation on Muscle Strength and Mass: A Systematic Review

Abstract: Anderson, OK, Martinez-Ferran, M, Lorenzo-Calvo, J, Jiménez, SL, and Pareja-Galeano, H. Effects of nitrate supplementation on muscle strength and mass: a systematic review. J Strength Cond Res 36(12): 3562–3570, 2022—This systematic review examines the effect of dietary nitrate supplementation (SUP) on muscle strength and hypertrophy when combined with physical exercise. The databases PubMed, Web of Science, and MEDLINE were searched for full-text articles published between January 2000 and June 2020. For incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This study was designed as a randomized, double-blind and placebo-controlled trial study in order to evaluate the potential effects of the combination 3 g/day of CIT plus 2.1 g/day of BR (300 mg/day of NO 3 − ) on sports performance during 9 weeks via several tests: HJUMP, DYN, 1-MAT and the Cooper test. The doses and supplementation time proposed for this study were based on studies that had found favourable results with similar doses [ 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was designed as a randomized, double-blind and placebo-controlled trial study in order to evaluate the potential effects of the combination 3 g/day of CIT plus 2.1 g/day of BR (300 mg/day of NO 3 − ) on sports performance during 9 weeks via several tests: HJUMP, DYN, 1-MAT and the Cooper test. The doses and supplementation time proposed for this study were based on studies that had found favourable results with similar doses [ 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these two supplements (CIT and BR) have been extensively studied individually, showing improvements when supplemented acutely (30–60 min before exercise) or in the short-term (7 days to 4 weeks) [ 33 , 34 , 35 ]. However, a possible combination of both for long-term (9 weeks), could further improve performance than either CIT or BR separately.…”
Section: Introductionmentioning
confidence: 99%
“…This study was planned as a randomized, double-blind, placebo-controlled trial to assess the impact of a 9-week oral supplementation of the combination of CIT plus BR on recovery status by distance-covered performance test, EIMD markers and anabolic/catabolic hormones in this sport population. The proposed doses of CIT (3 g/day) and BR supplements were based on previous scientific studies that found favorable results with similar doses [ 42 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Yet, the meta-analysis by Wong et al [30] revealed no changes in power during high-intensity interval training. Additionally, look at more recent review and meta-analysis papers on nitrate supplementation [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%